2010
DOI: 10.1155/2010/908649
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Levels of TNF-Alpha and IL-6 Long after Delivery in Preeclamptic and Normotensive Pregnant Women

Abstract: Aim. To evaluate maternal TNF-alpha and IL-6 plasma levels in normotensive pregnant women, women with preeclampsia, and to examine the temporal changes in their levels from theantepartum to the postpartum period correlated with the regression of preeclampsia. Method. A prospective study was performed in the 2nd Department of Obstetrics and Gynecology, University of Athens. Blood samples were obtained: (1) antepartum at the time of clinical diagnosis of the syndrome, 2. 12-14 weeks postpartum. Results. No stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 42 publications
4
57
0
4
Order By: Relevance
“…It is known that this cytokine induces trophoblastic apoptosis, through the overproduction of free radicals by macrophages and monocytes [32]. Thus, it is expected that the serum levels of this cytokine would be elevated in PE [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that this cytokine induces trophoblastic apoptosis, through the overproduction of free radicals by macrophages and monocytes [32]. Thus, it is expected that the serum levels of this cytokine would be elevated in PE [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this cytokine induces trophoblastic apoptosis, through the overproduction of free radicals by macrophages and monocytes [32]. Thus, it is expected that the serum levels of this cytokine would be elevated in PE [32,33]. Roudsari et al [34], assessing TNF-a, did not find a statistically significant difference between pregnant women with PE and their normotensive peers, observing low and stable serum levels during pregnancy; their results are in agreement with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…First, a higher plasma sST2 concentration may be a consequence of an intravascular inflammatory response which is exacerbated in preeclampsia when compared to an uncomplicated pregnancy [23,25,[168][169][170]. Indeed, it has been demonstrated that pro-inflammatory cytokines are increased in the plasma or serum of women with early-onset preeclampsia [35,41,42] and severe preeclampsia [36,40,41] when compared to women with uncomplicated pregnancies. Moreover, IL-1b or TNF-a (pro-inflammatory cytokines which are increased in preeclampsia) are able to stimulate vascular endothelial cells to secrete sST2 into supernatant [146,147].…”
Section: Plasma Concentrations Of Soluble St2 Is Elevated In Preeclammentioning
confidence: 99%
“…A defect of deep placentation [9][10][11][12][13] is proposed to generate utero-placental ischemia [14][15][16], placental endoplasmic reticulum and oxidative stress [17][18][19][20][21][22], and subsequently systemic intravascular inflammation [23][24][25] and endothelial dysfunction [17,[26][27][28][29][30][31][32][33][34]. The circulating concentrations of pro-inflammatory cytokines, such as interleukin (IL)-1-b and tumor necrosis factor (TNF)-a [35][36][37][38][39], as well as other inflammatory mediators (such as IL-6) [36,[40][41][42] are typically elevated in patients with preeclampsia, although this is not a universal feature [43,44]. The placenta is essential for the development of preeclampsia, while the fetus is not [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-a inhibits decidual invasion by cytotrophoblasts, stimulates cell proliferation and hypoxia-mediated cell activation. It also induces structural and functional alterations in endothelial cells, endothelin-1 (ET-1) production and inhibition of acetylcholine induced vasodilatation [11,12].…”
Section: Introductionmentioning
confidence: 99%